2022
DOI: 10.1177/10775463211056833
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive output regulation of the adaptive optics system

Abstract: Deformable mirrors are very efficient optical devices that are used in correcting wavefront aberrations and are core elements of adaptive optics systems. Its promising success allows it to operate in a large field of applications. Hence, one of the most important problems in the control of adaptive optics systems is to design a controller that can achieve perfect wavefront correction in completely unknown environmental conditions. To achieve this goal, this study proposes an adaptive internal model control des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This technology has been developed in the astronomy field to add or remove aberration from the incident wavefront and allowing the telescope to boost image resolution by correcting the dynamic wavefront distortion caused by atmospheric turbulence. Owing to its benefits, AO is widely employed in the civil, industrial, and medical fields [14][15][16] and it has been demonstrated to improve laser processing material capabilities [17].…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been developed in the astronomy field to add or remove aberration from the incident wavefront and allowing the telescope to boost image resolution by correcting the dynamic wavefront distortion caused by atmospheric turbulence. Owing to its benefits, AO is widely employed in the civil, industrial, and medical fields [14][15][16] and it has been demonstrated to improve laser processing material capabilities [17].…”
Section: Introductionmentioning
confidence: 99%